PEMBELAJARAN OUTDOOR LEARNING UNTUK KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS V SD - Erisy Syawiril Ammah; Sudarsri Lestari (PGMI Department of Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2024)
This research aims to describe outdoor learning for expository text writing skills in fifth grade elementary school students. The research uses a qualitative approach. Primary data was obtained from observations and interviews with 23 students and an Indonesian language subject teacher for class V, while secondary data was obtained from documentation of teaching modules, supporting books and curriculum tools used. The research results show that outdoor learning for expository text writing skills is carried out through three main stages, namely preparation, implementation and evaluation. In the preparation stage, the teacher prepares teaching modules and analyzes a series of risks that can arise when implementing outdoor learning. At the implementation stage, learning activities are divided into two meetings, first to deliver material related to exposition texts, and second to implement outdoor learning and student activities to produce exposition texts. At the evaluation stage, there are three things that are the focus of activities. First, evaluate the implementation of learning. Second, evaluate student responses and feedback. Third, evaluation of the results of expository text writing skills obtained through outdoor learning.